(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the antimicrobial potential of the aqueous extract of green propolis in vitro against mastitis-causing and in vivo bacteria, evaluating the efficacy of treatment in Lacaune sheep. In the in vitro test, the minimum inhibitory concentration (MIC) was used; first, the MIC was obtained from the aqueous extract of green propolis for the strain of Staphylococcus. aureus ATCC 25523, defined as 1 mg/ml. For bacterial agents isolated from sheep with mastitis (Staphylococcus epidermidis, Staphylococcus intermedius, Staphylococcus hyicus, Corynebacterium spp. and Acinetobacter spp.), The concentration of 10 mg/ml was determined, while for Streptococcus equinus, Escherichia coli, and hemolytic E. coli, also isolated from sheep with mastitis, the concentration capable of reducing bacterial growth was 100 mg/ml. In the in vivo test, ten sheep were used, distributed in two treatments, five in the control group (CG) that received 2.5 ml of saline (vehicle), and five in the treated group (GT) that received 2.5 ml of aqueous (saline) propolis extract by the mammary route. The propolis dose tested (0.1 g/ml) was not effective for the treatment of mastitis, because the sheep remained positive in the racket test (CMT). The main microorganism isolated in the cases of mastitis in this study was Staphylococcus epidermidis. These results are preliminary; however, at the tested dose, the aqueous extract of green propolis delivered by the mammary route had no curative effect of mastitis.